Gender differences in autonomic and psychological stress responses among educators: a heart rate variability and psychological assessment study - Calderón-García, Andrea; Álvarez-Gallardo, Estela; Belinchón-deMiguel, Pedro; Clemente-Suárez, Vicente Javier (Frontiers in Psychology, 2024)
Introduction This study explores the gender differences in psychological stress perception and autonomic modulation among teachers. Methods Utilizing heart rate variability (HRV) as a measure of autonomic function and a suite of validated psychological tests, the study examines the discrepancies in stress, anxiety, burnout, and personality traits between male and female educators. Results Results indicate that despite higher reported levels of stress and anxiety, women demonstrate a higher HRV, suggesting a stronger parasympathetic response. Discussion These findings highlight the complex interplay between psychological stressors and physiological responses, emphasizing the need for gender-specific interventions in stress management within the educational sector. Implications for enhancing educators’ well-being and performance through tailored strategies are discussed.